2003
DOI: 10.1002/jemt.10345
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization and polyspermy in the pig: Factors affecting fertilization rates and cytoskeletal reorganization of the oocyte

Abstract: Polyspermy is a common phenomenon in the pig. Extensive information has become available from in vitro studies on not only the quality of oocytes but also the quality of spermatozoa. However, little information is available on the relative penetration rates of fresh and frozen spermatozoa from the same ejaculate from boars of different breeds. The present results, based on a total of 15 boars of three different breeds, revealed that the inter-breed variation in fertilization and polyspermic rates is larger tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 38 publications
3
39
1
Order By: Relevance
“…The characteristics of actin microfilaments observed both in immature (at germinal vesicle stage) and mature (MII) oocytes were similar to those previously described in porcine oocytes [34,35]. Minor differences were observed by CLSM in actin microfilament patterns in mature oocytes after treatment.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The characteristics of actin microfilaments observed both in immature (at germinal vesicle stage) and mature (MII) oocytes were similar to those previously described in porcine oocytes [34,35]. Minor differences were observed by CLSM in actin microfilament patterns in mature oocytes after treatment.…”
Section: Discussionsupporting
confidence: 84%
“…1A-F). These criteria were adapted from previous studies [33][34][35]. Blastocysts were classified into grades I to III according to the integrity of their actin cytoskeleton, as previously described [28,36,37].…”
Section: Classification Of Actin Stainingmentioning
confidence: 99%
“…Although high polyspermic penetration rates are well documented in pigs (FUNAHASHI 2003;SUZUKI et al, 2003), some interesting interactions of oocyte quality and the sire have been reported in cattle (OHLWEILER et al, 2013), where depending on the technique used to artificially fertilize the oocyte, the embryo development rate was affected or not by the oocyte quality. Unfortunately, oocytes of low quality are predominant in gilt ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Great variations have been observed in polyspermy rates of both fresh (SIRARD et al, 1993) and frozen semen (NAGAI et al, 1988). Polyspermy rates are directly related to the sperm number at the site of fertilization (FAUSTINI et al, 2010), and also with the oocyte quality (SUZUKI et al, 2003). It is believed that the oviduct microenvironment participates in polyspermic blocking during in vivo fertilization (LUÑO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation